On limit cycles bifurcating from the infinity in discontinuous piecewise linear differential systems - Gouveia, Márcio R.A. [UNESP]; Llibre, Jaume; Novaes, Douglas D. (Elsevier, 2015)
In this paper we consider the linear differential center (x,y)=(-y,x) perturbed inside the class of all discontinuous piecewise linear differential systems with two zones separated by the straight line y=0. Using the Bendixson transformation we provide sufficient conditions to ensure the existence of a crossing limit cycle coming purely from the infinity. We also study the displacement function for a class of discontinuous piecewise smooth differential system.
Keywords: Discontinuous differential system; Displacement function; Infinite periodic orbit; Limit cycle; Piecewise linear differential system